Insertion Element IS3-Based PCR Method for Subtyping Escherichia coli O157:H7 - Thompson, Curt J. (American Society for Microbiology, 1998)
An Escherichia coli O157:H7 subtyping method based on PCR amplification of variable DNA sequences between the repetitive element IS3 was developed. Template DNA was prepared by boiling cells in Chelex. Two separate IS3 PCR amplifications were performed for each isolate: one with a single primer (primer IS3A) and one with two primers (primers IS3A and IS3B). The IS3 PCR subtyping method was applied to 35 epidemiologically related and unrelated E. coli O157:H7 isolates that had been previously characterized by pulsed-field gel electrophoresis (PFGE). PFGE identified 25 different subtypes (difference of one or more bands). PCR with single primer IS3A and primer pair IS3A-IS3B identified 6 and 14 different subtypes, respectively. By combining the results of the two PCR amplifications, 15 different IS3 PCR subtypes were identified. While not as sensitive as PFGE, IS3 PCR subtyping grouped all outbreak-related isolates. IS3 PCR banding patterns were reproducible between amplifications and between subcultures. IS3 PCR could serve as a simple, rapid screening method for the identification of unrelated E. coli O157:H7 isolates.